2017
DOI: 10.18632/oncotarget.16252
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide is a potential therapeutic for familial adenomatosis polyposis by disrupting Axin-GSK3 interaction

Abstract: The epithelial-mesenchymal transition (EMT) is implicated in tumorigenesis and cancer progression, and canonical Wnt signaling tightly controls Snail, a key transcriptional repressor of EMT. While the suppression of canonical Wnt signaling and EMT comprises an attractive therapeutic strategy, molecular targets for small molecules reverting Wnt and EMT have not been widely studied. Meanwhile, the anti-helminthic niclosamide has been identified as a potent inhibitor of many oncogenic signaling pathways although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…That study further indicated that CD10 may play a certain role during the EMT by Twist1 . Actually, niclosamide was also reported to inhibit the EMT in breast cancer and colon cancer cells . Our results showed that knockdown or overexpression of Twist in SK‐Hep‐1 and Huh7 cells respectively downregulated and upregulated CD10 expression.…”
Section: Discussionsupporting
confidence: 67%
“…That study further indicated that CD10 may play a certain role during the EMT by Twist1 . Actually, niclosamide was also reported to inhibit the EMT in breast cancer and colon cancer cells . Our results showed that knockdown or overexpression of Twist in SK‐Hep‐1 and Huh7 cells respectively downregulated and upregulated CD10 expression.…”
Section: Discussionsupporting
confidence: 67%
“…Next, the role of cWnt signaling on A/V axial patterning was examined using a loss‐of‐function study. Treatment with 10 μM niclosamide (5‐chloro‐ N ‐(2‐chloro‐4‐nitrophenyl)‐2‐hydroxybenzamide), a cWnt signaling inhibitor (Ahn et al, ; Chen et al, ; Mook et al, ), from early gastrulation caused the ectodermal and endomesodermal cell layers to develop in an abnormal shape and strongly expanded vegetal expression of foxq2 (Figures S2A and S2D). In contrast, brachyury expression became narrow compared with that of control embryos (Figures S2B and S2E).…”
Section: Resultsmentioning
confidence: 99%
“…Mebendazole can be administered with the non-steroidal anti-inflammatory drug sulindac for prevention of tumor initiation in a colon cancer model [33]. Colon Cancer [52] Breast Cancer Triple [29] Breast Cancer [53] Adrenocortical Cancer [19] Adrenocortical Cancer [39] Leukemia/Myeloma [25] Leukemia/Myeloma [34] Leukemia/Myeloma [59,64] NSCLC [20] NSCLC [36] Lung Cancer CSC [57] Cell Lines [9] Cancer stem cells [46] Cancer [61] Gastric Cancer [22] Osteosarcoma [37] Medulloblastoma [23] Prostate Cancer [36] Melanoma [21,29] Ovarian Cancer/ TICs [41 -44] Ovarian cancer [62] Breast CSC-like Cells [26] Breast CSC-like Cells [40] Breast CSC-like Cells [56] Glioblastoma [24,32] Glioblastoma [33] Glioblastoma CD133 + [60] This table lists reports on investigations employing mebendazole, niclosamide and pyrvinium (pamoate) as anticancer agents against cell lines or in experimental animal models.…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 99%
“…Furthermore, niclosamide inhibited not only signal transduction, but also targeted mitochondria in cancer cells resulting in cell cycle arrest, growth inhibition and apoptosis [49 -51]. Niclosamide may work as therapeutic for familial adenomatosis polyposis (FAP) by disrupting the axin-GSK3 interaction and for colon cancer in synergizing with erlotinib [52,53]. Accordingly, clinical trials administrating niclosamide for the treatment of resectable/metastatic colon cancer and castration-resistant, metastatic prostate cancer are recruiting.…”
Section: Anticancer Activity Of Niclosamidementioning
confidence: 99%
See 1 more Smart Citation